2016
DOI: 10.3844/ajbbsp.2016.64.71
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length Measurement by Quantitative Real-time PCR: A Molecular Marker for Human Age Prediction

Abstract: The fact that telomere shortening occurs with aging leads to the hypothesis that a correlation could be made between Telomere Length (TL) and suspect age. This study aimed to assess if TL can be used as an investigational tool to predict human age through developing a formula based on this correlation with accuracy suitable to be applied in forensic practice. A quantitative real-time PCR study was carried out on 80 Egyptians, ranging in age from 1-79 years. The results confirmed that the relative TL significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In both scenarios, such a characteristic has been considered a marker of cellular senescence 35, 63 . Relative telomere length was determined using two established methods 34, 45, 46 in the chorioamniotic membranes from the four study groups. The validation of the relative telomere length methods showed that both sets of primers are able to detect senescent cells: the older individual had a shorter telomere length than the younger individual (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both scenarios, such a characteristic has been considered a marker of cellular senescence 35, 63 . Relative telomere length was determined using two established methods 34, 45, 46 in the chorioamniotic membranes from the four study groups. The validation of the relative telomere length methods showed that both sets of primers are able to detect senescent cells: the older individual had a shorter telomere length than the younger individual (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Relative telomere length was also measured in the same samples using a different qPCR method and primers 34, 46 . The primers (hereafter referred to as “Primer Set#2”) used to amplify the telomere region were the following: forward (5′-CGG TTTGTTTGGGTTTGGGTTTGGGTTTGGGTTTGGGTT-3′) (200nM) and reverse (5′-GGCTTGCCTTACCCTTACCCTTACCCTTACCCTTACCCT-3′) (200nM).…”
Section: Methodsmentioning
confidence: 99%